Understanding the role of ursodeoxycholic acid and gut microbiome in non-alcoholic fatty liver disease: current evidence and perspectives - Mao, Qingyi; Lin, Beibei; Zhang, Wenluo; Zhang, Yu; Zhang, Yu; Cao, Qian; Xu, Mengque (Frontiers in Pharmacology, 2024)
Non-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease, resulting in a huge medical burden worldwide. Accumulating evidence suggests that gut microbiome and bile acids play pivotal roles during the development of NAFLD. Patients with NAFLD exhibit unique signatures of intestinal microbiome marked by the priority of gram-negative bacteria, decreased ratio of Firmicutes/Bacteroidetes (F/B), and increased Prevotella and Lachnospiraceae. The intestinal microbiota is involved in the metabolism of bile acids. Ursodeoxycholic acid (UDCA)is a key determinant in maintaining the dynamic communication between the host and gut microbiota. It generally shows surprising therapeutic potential in NAFLD with several mechanisms, such as improving cellular autophagy, apoptosis, and mitochondrial functions. This action is based on its direct or indirect effect, targeting the Farnesoid X receptor (FXR) and diverse other nuclear receptors. This review aims to discuss the current studies on the involvement of microbiome-UDCA interface in NAFLD therapy and provide prospective insights into future preventative and therapeutic approaches for NAFLD.